Studi kandungan senyawa tributiltin dalam air pada area budidaya di Selat Lembeh Bitung - Simanjorang, Daniel; Undap, Suzanne L.; Tumembouw, Sipriana S.; Pangemanan, Pankie N.L; Pangkey, Henneke; Mudeng, Joppy D. (Universitas Sam Ratulangi, 2025)
Tributiltin (TBT) is an organotin compound that is still widely used as a toxic biocidal additive in antifouling paints. These compounds are classified as pollutants that are very difficult to decompose in waters. The test of the concentration of TBT in seawater was carried out at the WLN Laboratory (Water Laboratory Nusantara) Manado. Nitrate, nitrite and ammonia concentration tests were carried out at the Laboratory of the Manado Industrial Service and Standardization Center (BSPJI). Measurement of the physical and chemical parameters of seawater used: Temperature, Brightness, pH, Dissolved Oxygen (DO), Salinity and Turbidity in situ. Analysis of the concentration of Tributiltin (TBT) compounds in seawater in the waters of the Lembeh Strait in the cultivation areas of Point 1 (Tanjung Rarandam), Point 2 (Kalapa Dua), Point 3 (Papusungan) in the Lembeh Strait showed a concentration of <0.01 μg/L, which is still in the safe range below the standard limit of seawater quality for biota (0.01 μg/L). Measuring water quality in the Lembeh Strait aquaculture area, the DO value ranges from 7.83-8.34 ppm. Salinity values ranged from 30.99-31.24 ppt. The pH value ranges from 9.37-9.42. The temperature value ranges from 27.87-27.69 °C. The brightness value ranges from 3.12 m-3.39 m. The turbidity value ranged from 0.63-1.22. The nitrate value of 1.98-2.19 mg/L, far exceeding the limit set (0.06 mg/L) for marine life, indicates a potential risk to the ecosystem. The concentration of Nitrite in the waters is still in accordance with the general water standards, ranging from <0.005 mg/L to 0.02 mg/L. The concentration of Ammonia is below the water quality standard threshold at all points of 0.3 mg/L, which is still safe for marine life and aquaculture activities in these waters in accordance with the seawater quality standards in Government Regulation No. 22 of 2021 Attachment VIII concerning the Implementation of Environmental Protection and Management. Keywords: TBT Compounds, Concentration, Water Quality, Quality Standards, Straits